Impact of Managerial Trustworthy Behavior on Employee Engagement: Mediating Role of Perceived Insider Status - Liu, Defeng; Bakari, Haroon; Niaz, Maharukh; Zhang, Qianxiao; Shah, Imran Ahmed (Frontiers in Psychology, 2022)
This study examines the impact of managerial trustworthy behaviour on employees' engagement and the mediating role of perceived insider status. This study has adopted an exploratory research design and positivist philosophy. The data is collected from 205 healthcare staff working in public sector hospitals in Pakistan through survey questionnaires and have used a convenience sampling technique. Partial Least Square Structural equation modelling is used to analyse the data and test hypotheses. Results indicate that managerial trustworthy behaviour relates positively to employee engagement. Perceived insider status mediates the relationship between managerial trustworthy behaviour and employee engagement. The major limitation of this study is its cross-sectional design which limits the casualty. However, this study offers important insights regarding trust-building, engagement, and inclusion in the health sector. This study highlights the importance of trust-building among managers and employees. Managers who instil more trust in employees will garner more positive behaviours. This study offers fresh insights into managers' trustworthy behaviour toward employees' engagement and the employees' perceived insider status within their organisations.